2012
DOI: 10.3762/bjoc.8.194
|View full text |Cite
|
Sign up to set email alerts
|

trans-2-(2,5-Dimethoxy-4-iodophenyl)cyclopropylamine and trans-2-(2,5-dimethoxy-4-bromophenyl)cyclopropylamine as potent agonists for the 5-HT2 receptor family

Abstract: SummaryA strategy to replace the ethylamine side chain of 2,5-dimethoxy-4-iodoamphetamine (DOI, 1a), and 2,5-dimethoxy-4-bromoamphetamine (DOB, 1b) with a cyclopropylamine moiety was successful in leading to compounds with high affinity at the 5-HT2 family of receptors; and the more potent stereoisomer of the cyclopropane analogues had the expected (−)-(1R,2S)-configuration. Screening for affinity at various serotonin receptor subtypes, however, revealed that the cyclopropane congeners also had increased affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Although 25CN-NBOH is less selective than was reported previously in the literature (Hansen et al, 2014), we confirmed it is 23-fold selective for 5-HT 2A receptors vs. 5-HT 2C receptors, and has negligible affinity for non-5-HT 2 sites. Importantly, 25CN-NBOH is more selective than DOI, which is ~5-fold selective for 5-HT 2A in humans (Almaula et al, 1996; Pigott et al, 2012; Canal et al, 2013) and 12-fold selective in mice (Canal et al, 2013). Given the results obtained with 25CN-NBOH, it is reasonable to conclude that DOI disrupts temporal discrimination by activating 5-HT 2A but not 5-HT 2C receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Although 25CN-NBOH is less selective than was reported previously in the literature (Hansen et al, 2014), we confirmed it is 23-fold selective for 5-HT 2A receptors vs. 5-HT 2C receptors, and has negligible affinity for non-5-HT 2 sites. Importantly, 25CN-NBOH is more selective than DOI, which is ~5-fold selective for 5-HT 2A in humans (Almaula et al, 1996; Pigott et al, 2012; Canal et al, 2013) and 12-fold selective in mice (Canal et al, 2013). Given the results obtained with 25CN-NBOH, it is reasonable to conclude that DOI disrupts temporal discrimination by activating 5-HT 2A but not 5-HT 2C receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The polypharmacological profiles of these drugs complicate their use as pharmacological tools for studies of physiologic 5-HT 2A R functions. Thus far, the prototypic 5-HT type 2 receptor (5-HT 2 R) agonist (6)-2,5-dimethoxy-4iodoamphetamine (DOI) has been used extensively to probe 5-HT 2A R functions in vivo; however, since DOI only displays modest preference for 5-HT 2A R over 5-HT 2B R and 5-HT 2C R (Almaula et al, 1996;Nelson et al, 1999;Pigott et al, 2012;Canal et al, 2013) it has often been applied in combination with 5-HT 2 R subtype-selective antagonists in previous studies. Because of its inherent selectivity for 5-HT 2 Rs over other serotonergic and monoaminergic receptors, the phenethylamine scaffold has often been applied as a lead in the search for selective 5-HT 2A R agonists (Rickli et al, 2015;Nichols, 2016), but the fact that the orthosteric sites in the three 5-HT 2 R subtypes are highly conserved has made the development of truly 5-HT 2A R-selective agonists difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The potent 5-HT 2A R agonist activity present in the amphetamine class has been thoroughly characterized, and the bioavailability and CNS exposure of DOI upon systemic administration has rendered it the 5-HT 2A R agonist of choice for animal investigations. [3,[18][19][20][21][22][23][24][25][26] As the compound contains an iodine atom at the 4'-position the structure also lends itself to radiolabeling, and the more bioactive R enantiomer has been used as a radioligand for autoradiography studies in rat brain. [27] However, although easily accessible and pharmacologically well-characterized, DOI only displays modest selectivity towards the recombinant 5-HT 2A R over the recombinant 5-HT 2B R and 5-HT 2C R in binding and functional assays (Table 1), a characteristic that occasionally is overlooked in interpretations of the in vivo effects of DOI.…”
Section: -Ht 2a R Agonist Tool Compoundsmentioning
confidence: 99%
“…[27] However, although easily accessible and pharmacologically well-characterized, DOI only displays modest selectivity towards the recombinant 5-HT 2A R over the recombinant 5-HT 2B R and 5-HT 2C R in binding and functional assays (Table 1), a characteristic that occasionally is overlooked in interpretations of the in vivo effects of DOI. [3,[18][19][20][21][22][23][24][25][26] In the quest for more sub-type selective tool agonists for the 5-HT 2A R medicinal chemistry exploration has yielded several sub-type selective scaffolds most notably the Benzylpiperidines and the N-Benzylphenethylamines. 2-(2,5-dimethoxy-4-bromobenzyl)-6-(2-methoxyphenyl)piperidine (DMBMPP, see Scheme 1) represents the former and is one the most selective agonists reported to date, with high binding affinity to 5-HT 2A R (K i = 2.5 nM) and 124-fold selectivity towards the 5-HT 2C R, although functional data is yet to be reported.…”
Section: -Ht 2a R Agonist Tool Compoundsmentioning
confidence: 99%